Patulin in homogenized fruit's and tomato products. (January 2016) - Sarubbi, Fiorella; Formisano, Giorgio; Auriemma, Giuseppe; Arrichiello, Assunta; Palomba, Raffaele
Abstract: Patulin is a mycotoxin produced by microscopic fungi belonging to the Penicillium and Aspergillus genera. The natural occurrence of patulin in baby food products marketed in Italy is frequently detectable in moldy fruits and their derivatives. The EC Regulation 1881/06 has limited the presence of patulin in baby food to 10 μg/kg or 10 μg/L on the basis of a Provisional Maximum Tolerable Daily Intake (PMTDI) of 0.4 μg/kg BW set by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). A total of 80 homogenized baby foods were analyzed to evaluate the exposure of babies to patulin through the consumption of these products. The experimental tests have revealed significant differences between the products from organic production and those in traditional production in all the categories analyzed. The tomato concentrates showed an average of patulin concentration of 7.15 ng/ml of product; the tomato sauce of 4.05 ng/ml; the tomato sauce to the baby foods of 5.23 ng/ml; the homogenized apple of 0.85 ng/ml; the homogenized pear of 0.79 ng/ml. The tomato sauce conventional vs organic crops showed an average of 5.75 vs 3.49 ng/ml, respectively; the homogenized pear conventional vs organic ones of 0.72 vs 0.76 ng/ml, respectively; the homogenized apple conventional vs organic ones of 1.92 vs 0.13 ng/ml, respectively. The low incidence of the patulin level in Italian products is a clear parameter to establish the quality of the fruits and their derived products. Highlights: Patulin is a mycotoxin produced by microscopic fungi. In baby food is frequently detectable in moldy fruits and their derivatives. The results show differences between the organic products and those traditional. The incidence of patulin levels is a parameter to assess the quality of the fruit.